The Effects of Low-Energy Moderate-Carbohydrate (MCD) and Mixed (MixD) Diets on Serum Lipid Profiles and Body Composition in Middle-Aged Men: A Randomized Controlled Parallel-Group Clinical Trial - Michalczyk, Małgorzata Magdalena; Maszczyk, Adam; Stastny, Petr (International journal of environmental research and public health, 2020)
Carbohydrate-restricted diets have become very popular due to their numerous health benefits. The aim of this study was to determine the influence of 4 weeks of a well-planned, low-energy moderate-carbohydrate diet (MCD) and a low-energy mixed diet (MixD) on the lipoprotein profile, glucose and C-reactive protein concentrations, body mass, and body composition in middle-aged males. Sixty middle-aged males were randomly assigned to the following groups: hypocaloric MCD (32% carbohydrates, 28% proteins, and 40% fat), hypocaloric MixD (50% carbohydrates, 20% proteins, and 30% fat), and a conventional (control) diet (CD; 48% carbohydrates, 15% proteins, and 37% fat). The participants who were classified into the MCD and MixD groups consumed 20% fewer calories daily than the total daily energy expenditure (TDEE). Baseline and postintervention fasting triacylglycerol (TG), LDL (low-density lipoprotein) cholesterol (LDL-C), HDL (high-density lipoprotein) cholesterol (HDL-C), total cholesterol (tCh), glucose (Gl), and C-reactive protein were evaluated. Body mass (BM) and body composition changes, including body fat (BF), % body fat (PBF), and muscle mass (MM), were monitored. Compared with MixD and CD, MCD significantly changed the fasting serum concentrations of TG (p < 0.05), HDL-C (p < 0.05), LDL-C (p < 0.05), tCh (p < 0.05), and glucose (p < 0.01). Additionally, body fat content (kg and %) was significantly reduced (p < 0.05) after MCD compared with MixD and CD. After the MixD intervention, BM and MM decreased (p < 0.05) compared with baseline values. Compared with baseline, after the MixD, BM, MM, tCh, LDL-C, and TG changed significantly. The 4 week low-energy MCD intervention changed lipoproteins, glucose, and body fat to a greater extent than the low-energy MixD. A hypocaloric MCD may be suggested for middle-aged male subjects who want to lose weight by reducing body fat content without compromising muscle mass.
Keywords: lidé středního věku; HDL-cholesterol; dietní proteiny; Weight Loss; mužské pohlaví; cholesterol; Obesity; Humans; Dietary Carbohydrates; Triglycerides; Diet, Fat-Restricted; carbohydrate-restricted diet; triglyceridy; lidé; Dietary Proteins; Lipids; Male; Middle Aged; dieta s omezením tuků; dietní sacharidy; Body Composition; body fat; Cholesterol, HDL; low energy; weight loss; lipidy; hmotnostní úbytek; obezita; složení těla